Clinical and pathological features of 5 cases of children pigmento-genes pityriasis rosea - Ting ZHANG; Xinni ZHONG; Lei ZHU; Yingying QIAN; Yafen WU; Wei LI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To analyze clinical manifestations and histopathological features of children patients with pigmento-genes pityriasis rosea. Methods Clinical manifestations, histopathological features and therapeutic responses were retrospectively analyzed for 5 patients, including 1 males and 4 females patients, with pigmento-genes pityriasis rosea. Results The age of onset was 5-16 years old, and the average age was 9.4 years old, the course of disease was from 1 month to 6 years. Long axes of lesions were oriented in planes of cleavage, running parallel to the dermatoglyph. Lesions were distributed over the trunk and proximal extremities. The increase of melanocyte and hyperkeratosis were the typical histopathological characteristics. Conclusions Pigmento-genes pityriasis rosea can be diagnosed according to clinical manifestations and histopathology. Vitamin c, vitamin E and antihistamine drugs are effective for children patient with pigmento-genes pityriasis rosea.